Game meat production in the Xhariep district of the Free State province : evaluating and optimising resources - Derbyshire, Walter ([Bloemfontein?] : Central University of Technology, Free State, 2011)
In addition to one national park and six nature reserves, the Free State Province boasts several privately owned game reserves, as well as game farmers and commercial stock farmers who keep game. A survey conducted in 1985 showed that the majority of game could be found in the Xhariep District situated in the southern and south-western parts of the province. Game export abattoirs and processing facilities are situated in provinces other than the Free State, which results not only in an outflow of game carcasses for export purposes, but also a loss of employment opportunities and opportunities for the generation of foreign currency from a district (Xhariep) which, from a socio-economic perspective, is seen as deprived. There are 21 non-export highthroughput red meat abattoirs in the province, posing the question as to whether these could be used for the slaughtering of game. This study aimed firstly to compile guidelines for the wild game meat industry regarding the production of wild game meat for the international market and to assess wild game production and utilisation in the Xhariep District through a comprehensive survey of game farming practices, game numbers and species, as well as the utilisation of game through various consumptive and non-consumptive methods. A further aim was to investigate practices at existing slaughter facilities in order to determine their potential to be adapted into wild game meat export facilities and assess such potential via a standardised protocol. The research commenced with an investigation into processing and export requirements for wild game meat in South Africa through a literature study of all EU legislation, directives and other relevant literature on the subject, and provides comprehensive reference material for entrepreneurs and developers in the wild game meat industry. Methodologies utilised included audits to determine the extent to which abattoirs conform to the structural, operational and documentation meat hygiene requirements followed by the development of a novel assessment matrix for measuring the level of compliance of existing abattoirs and their potential to be developed into European Union (EU) export facilities. The survey of the Xhariep area concluded that a significant potential exists for the expansion of the game industry, as several respondents indicated that they were interested in expanding their game production and that they had land available for this purpose. A further indication was that the game would be highly marketable because it was free ranging and could be regarded as organic due to the absence or controlled use of additives and pesticides that could result in chemical residues in the meat. The establishment of a wild game export facility was favoured by nearly 70% of the respondents. The hygiene evaluation of existing slaughter facilities in the Free State Province resulted in six slaughtering facilities being rated as good or excellent, demonstrating the potential to successfully process game meat for the export market. This was tested by utilising the proposed evaluation matrix, which rated the abattoirs most suited to be adapted into game meat processing facilities for export purposes. The value of this approach lies in the fact that it is not only restricted to local markets, but can be utilised internationally by the abattoir industry, as well as the fact that it is not species specific. It should, however, be applied objectively by knowledgeable operators in the industry. It is concluded that institutions in the Free State Province possess the knowledge and ability to not only produce wild game meat, but also to successfully process this commodity through the optimal utilisation of existing high-throughput red meat abattoirs. By utilising existing management skills and affecting relatively minimal adjustments to existing structures, these resources should be utilised to successfully enter the wild game meat export market which should, in turn contribute towards the prosperity of the Xhariep District.
Thesis (D. Tech. Environmental health) -- Central University of technology, Free State, 2011
Keywords: Central University of Technology, Free State - Dissertations; Meat industry and trade - South Africa - Free State; Wildlife as food; Meat - Quality; Game and game-birds - South Africa - Free State; Dissertations, academic - South Africa - Bloemfontein